2009
DOI: 10.1007/s11195-009-9112-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Identity, Body Image and Life Satisfaction Among Women With and Without Physical Disability

Abstract: The current study examined the association between sexual identity, body image and life satisfaction among women with and without physical disability. Seventy women with physical disability (spinal cord injuries and injuries resulting from polio) and 64 women without disability completed the following questionnaires: Sexuality Scale, Body Image Scale and Quality of Life Questionnaire. The results demonstrated that women with physical disability had the same sexual needs and desires as women without disability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 24 publications
(37 reference statements)
2
67
0
4
Order By: Relevance
“…These findings build on previous research that demonstrated a link between general self-esteem and subjective well-being (Moin et al, 2009). Moin and colleagues compared women with physical disabilities and women without physical disabilities in relation to sexual identity, body image and life satisfaction.…”
Section: Summary Of Major Findingssupporting
confidence: 89%
See 3 more Smart Citations
“…These findings build on previous research that demonstrated a link between general self-esteem and subjective well-being (Moin et al, 2009). Moin and colleagues compared women with physical disabilities and women without physical disabilities in relation to sexual identity, body image and life satisfaction.…”
Section: Summary Of Major Findingssupporting
confidence: 89%
“…Moin and colleagues compared women with physical disabilities and women without physical disabilities in relation to sexual identity, body image and life satisfaction. The researchers found that the way individuals feel about our sexual selves influences the manner in which we perceive our lives (Moin et al, 2009). In an additional study, Moksnes and Espnes (2013) assessed secondary school students in Europe found that general self-esteem contributed to subjective well being across participants with different gender, age, stress, subjective health and chronic mental health conditions.…”
Section: Summary Of Major Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have compared life satisfaction of people with long-standing SCI with that of the general population (Figure 1). 14,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The differences between mean scores in people with SCI and in the population are expressed as effect sizes. 45 The mean effect size of all studies in Figure 1 is À0.77 (s.d.…”
Section: Methodsmentioning
confidence: 99%